Students' Evaluation of Simulation-Based Training in a Communication Sciences and Disorders Program. - Putter-Katz, Hanna; Gvion, Aviah; Wechsler-Kashi, Deena; Said, Limor Adi-Ben; Yaacobi, Hadas; Feldman, Irit; Shalomson, Orit; Ziv, Amitai (Journal of Allied Health)
The current study aimed to evaluate simulation-based medical education (SBME) training and its contribution to the learning process of students in a communication sciences and disorders (CSD) program. The training was integrated in different stages of the program, over 4 years, with different students. The content and complexity of each of the simulation activities targeted specific skills, tailored to the students' learning phase. Students completed a nine-item survey at the end of the first and second semesters of the second year, evaluating the simulation training program structure and students' self-efficacy relating to the building of relationships between care givers and patients. A total of 246 questionnaires were analyzed. Students reported significantly increased self-efficacy in a range of clinical skills and perceived the inclusion of simulated patients (SPs) into a clinical skills program as valuable. Our data suggest that scenarios that reflect real-life situations (environment, atmosphere, equipment, etc.) have the strongest impact on the students' ability to implement professional and communication skills. A strong positive correlation was found between the video-based debriefing and students' perception of the improvement in their professional and communication skills. These findings suggest that this is a feasible and powerful training approach that can be applied in the CSD curriculum.